GROUND INSECT DIVERSITY IN ARBORETRUM OF SUMBER BRANTAS BATU-MALANG AS BASE OF LEARNING RESOURCE MAKING: FLIPCHART - Rachmasari, Ovy Dwi; Prihanta, Wahyu; Susetyarini, Roro Eko (Jurnal Pendidikan Biologi Indonesia, 2016)
Forests are natural resources in which have high potencial support of biodiversity. One of the existing resources in the forest are ground insects. The presence ground insects are needed to aid in decomposition processes. The purpose of this study was to determine what kind of insects are there in the arboretum Sumber Brantas which its scientific classification can be determined based on their classification until species level. Moreover, to know the diversity value, the abundance, and the sum dominance ratio in three stations.This type of research is descriptive quantitative which employing observation technique in collecting data. Pitfall trap was used to trap ground insects.The results showed that the ground insects found in the study site were: 8 species of 4 orders, diversity index at the Arboretum Sumber Brantas Batu-Malang was moderate of 1.6597, the highest abundance values was at station I of 10.00 for Diplocheila polita, while the greatest percentage of sum dominace value was at station III for Periplaneta Americana of 0.89%. The resuls of the study were used to make flipchart as biology learning resources.